Geospatial Simulation On The Susceptibility Of Deped Schools To Storm Surge In Surigao Del Sur Province, Philippines (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Surigao Del Sur Is One Of The Coastal Provinces Of Caraga Region Identified As One Of The Top 30 Provinces In The Philippines With A High Storm Surge Level And Lecz Population Density.  The Possible Threat Imposed By This Kind Of Calamity Especially To Education Sector Compelled The Researcher To Undertake A Study On Identifying The Deped Schools Susceptible To Storm Surge. This Study Uses The Storm Surge Data From The Nationwide Operational Assessment Of Hazards (Project Noah) Which Is The Flagship Disaster Mitigation Program Of The Department Of Science And Technology (Dost) Of The Philippine Government. Along With The Generated Maps Of Digital Elevation Model (Dem) And Spatial Distribution Of Schools, This Study Simulates The Possible Storm Surge Height That The Deped Schools Are Prone To. Results Of The Study Revealed That Out Of 534 Schools Utilized In The Study, 96 (17.98%) Are Susceptible To Ssa-1, 128 (23.79%) Are Susceptible To Ssa-2, While 149 (27.9%)Are Susceptible To Ssa-3, And 161(30.15%) Are Susceptible To Ssa-4. Out Of The 17 Municipalities And 2 Cities In The Province,  Lingig Has The Highest Number Of Deped Schools Susceptible To Ssa-3 And Ssa-4, Followed By Hinatuan, City Of Bislig And City Of Tandag. Results In This Study Can Be The Basis For Provincial And City Deped Officials And Lgu’s Of Surigao Del Sur In Prioritizing A Site-Specific Management Plan To Address The Possible Storm Surge Hazard.